Duodenal mucosa and extracellular cyclic nucleotide pattern in coeliac disease. Issue 6 (June 1993) - Peracchi, M; Bamonti-Catena, F; Faggioli, P; Molteni, N; Bardella, M T; Bareggi, B; Bianchi, P A
Abstract : This study measured the values of cyclic nucleotides and adenylate and guanylate cyclase activities in duodenal mucosa homogenates to verify if they played a part in coeliac disease. Nine controls, 13 patients who did not receive treatment and nine patients who received treatment were studied. Cyclase activity assays were performed under basal conditions and in the presence of gliadin derived peptides. Duodenal mucosa cyclic nucleotide values and adenylate cyclase activity were significantly higher in patients who did not receive treatment than in those who did and in controls, whereas guanylate cyclase activity was similar in all groups. Gliadin derived peptides did not affect guanylate cyclase activity, but significantly increased adenylate cyclase activity in homogenates from patients who did not receive treatment. As extracellular cyclic nucleotide concentrations could reflect changes in their intracellular metabolism, plasma and urine cyclic nucleotide values were also measured in 25 controls and in 55 patients studied at different stages of their disease. Extracellular cyclic nucleotides were considerably high in patients who were not healed and became normal after about one year of treatment. These data suggest that cyclic nucleotides may participate in the pathophysiological processes of coeliac disease.